A Rare Case of Metastatic Solitary Fibrous Tumor (Hemangiopericytoma) of the Dura on 18F-FDG PET/CT. (September 2021) - Grünig, Hannes; Skawran, Stephan; Stolzmann, Paul; Messerli, Michael; Huellner, Martin W.
Abstract : Abstract: Solitary fibrous tumor is a rare neoplasm of mesenchymal origin. It can arise in various locations, most commonly in the pleura. It encompasses a heterogeneous group of histological patterns with different biological behavior. In some cases, metastases occur, sometimes years after the initial diagnosis. We report a case of metastatic meningeal hemangiopericytoma, also called solitary fibrous tumor of the dura, exhibiting liver metastases and muscle metastases 5 years after resection and adjuvant radiotherapy of the primary tumor.